A Microfluidic Approach for Quantitative Study of Spatial Heterogeneity in Bacterial Biofilms. Issue 10 (20th September 2022) - Zhang, Yuzhen; Cai, Yumin; Zeng, Lingbin; Liu, Peng; Ma, Luyan Z.; Liu, Jintao
Abstract : Bacterial biofilms play essential roles in ecological environments and in human health. The spatial heterogeneity of biofilms is crucial to their resistance and collective behavior, while quantitative analysis of these biofilm‐specific features is limited. Here, a microfluidic approach is developed to address this issue. Through a special design of microfluidic chamber and spatially controllable bacteria seeding, biofilms are cultivated with customized semi‐2D structure, which enables quantitative measurements of spatially heterogeneous features with time‐lapse microscopy. The advantages of the proposed method are demonstrated via two examples on biofilm homeostasis and stress response, respectively, where the functionally important spatiotemporal dynamics is delineated. In homeostasis, it is found that Pseudomonas aeruginosa biofilms use spatially organized extracellular matrix to preserve iron chelators within their boundaries while maximizing free sharing within the community. In stress response, the spatial distribution of antibiotics in biofilms and how a change in energy metabolism leads to redistribution of drugs over space are elucidated. The proposed method enables cultivating biofilms formed by a wide range of species and even multiple biofilms, which provides a tractable approach to understanding the spatiotemporal features of biofilms formed by environmentally and clinically important bacteria. Abstract : Spatial heterogeneity of biofilms is crucial to their resistance and collective behavior, while quantitative analysis of these biofilm‐specific features is limited. A microfluidic approach to address this issue is developed. Through a special design of microfluidic chamber and spatially controllable bacteria seeding, biofilms are cultivated with customized semi‐2D structure, which enables quantitative measurements of spatially heterogeneous features.